Exploring the "fold-in" strategy toward the construction of a highly-strained triazasumanene skeleton. Issue 18 (15th February 2017) - Chen, Fengkun; Tanaka, Takayuki; Osuka, Atsuhiro
Abstract : "Fold-in"-type syntheses toward the construction of tribenzotriazasumanene were attempted under oxidative and reductive conditions, which resulted in the formation of two different products. Abstract : The synthesis of tribenzotriazasumanene was attempted on the basis of the "fold-in" synthesis of cyclic pyrrole trimer5 and its analogues under oxidative and reductive conditions. While unexpectedly triply-fused product6 was obtained in the oxidation of5 with FeCl3 and AgOTf, the reductive coupling of hexabromo-tri- N -methylpyrrole trimer9 furnished partially fused product10 . These results indicate the potential of the "fold-in" strategy that gave complementary outcomes depending on the reaction conditions.